Decolourization properties of pure phases in hydrated cement paste for anionic dyes in textile wastewater - Martin Behringer; Harald Hilbig; Brigitte Helmreich; Alisa Machner (Heliyon)
The rise of fast fashion has increased the need for cost-effective adsorbents in textile wastewater treatment. Cementitious materials have shown promising decolourizing properties in anionic dye solutions. This study evaluates the decolourization properties of a selection of phases typically present in hydrated cement paste, such as calcium-(alumino)-silicate-hydrate (C-(A)-S-H) phases, hydrotalcite, and monocarboaluminate. Three anionic dyes were tested in combination with different salts, which are used in textile dyeing. Reactive Blue 19 was adsorbed more effectively than the other dyes. C-(A)-S-H phases performed best in basic environments, while layered structures excelled in acidic conditions, with monocarboaluminate reaching over 250 mg/g at pH 5. The presence of salts significantly affected adsorption, with MgSO4 mainly enhancing the decolourization up to 178 mg/g for monocarboaluminate and NaCl reducing capacities to a maximum adsorption of 95 mg/g for hydrotalcite. For hydrotalcite and monocarboaluminate, the effect of pH and presence of salts on the overall decolourization could be explained by a linear correlation between the zeta potential of the solid phases and their decolourization capacity. These findings provide valuable insights into the potential of cementitious materials as low-cost adsorbents in the treatment of coloured textile wastewater.